(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Many vehicles drive on the highway, and toll taxes must be collected as they pass by. However, this is a time-consuming operation, and poor management may result in long lines and pollution. By using Automation in Toll Collection, several solutions have been created to decrease the complexity of the operation. There are a number of systems available; we examine a few of them and look for areas where they might be improved. ATCSR is an RFID based Automated Toll Collection System that collects taxes automatically. We use radio frequency to perform the identification in this case. An RFID tag will be attached to a car. This tag is just an exceptional distinguishing number. The RTO, or traffic controlling power, will be responsible for this. We will record all principal data, as well as the sum he has paid ahead of time for the TOLL assortment, as per this number. At the cost assortment office, a peruser will be decisively situated. The assessment sum will be taken from the vehicle’s prepaid equilibrium at whatever point it goes through a tollgate. Another balance will be set up. On the off chance that one’s equilibrium is insufficient, his refreshed equilibrium will be negative. To resolve this issue, we have a camera out and about that catches the image of the significant vehicle. Since vehicles are not expected to stand by, gridlock at cost squares is limited, and fuel utilization is brought down. This is a critical advantage of this framework.